Outstanding hospitality marketing for the 'noughties' - de Safrin, Ashley (Henry Stewart Talks, 2009)
'Noughties' marketing, Is hospitality marketing so different?, Outstanding hospitality marketing, Who is the 'noughties' customer?, Getting started on the marketing journey or rethinking your customer proposition, Marketing tools for the 'noughties', Evaluating your effectiveness, Future challenges
Archived at 2022/04/07